Improvement the Strength Characteristics of Loose Sandy Soil Using Sustainable Geopolymer - Alaa H. J. Al-Rkaby, Ahmed Katea (Mathematical Statistician and Engineering Applications, 2023)
Loose sand present problematic ground condition, as a result of its low bearing capacity. Therefore, this paper investigated the strength of loose sand treated by geopolymer, which has introduced recently as a novel echo-friendly alternative to the tradition materials of soil stabilization such as lime and Ordinary Portland Cement (OPC) to eliminate their sever impacts on the environment. The results shows that the unconfined compressive strength of the loose sand-geopolymer matrix increased significantly in range of with increasing the main ingredient of the geopolymer, i.e. fly ash. Similar trend was observe regarding to the secant modulus. However, with increasing the activator ratio, the compressive strength of soil-geopolymer matrix decreased for fly ash content of 20-30% and increased when the fly ash was 5-15%. The improvement in the strength is attributed to the dense and stiff crystalline structure due to fill the sand voids by fly ash, produce gepolymer hydrated gel (C, N–A–S–H) that significantly bonded the soil particles. Therefore, geopolymer is viable sustainable material to improve such problematic soil for different applications.